Czynniki ryzyka zakażenia HCV oraz metody profilaktyki = Risk factors of HCV infection and methods of prevention - Marta Estera Kowalska; Paweł Kalinowski; Urszula Bojakowska (Kazimierz Wielki University, 2016)
Kowalska Marta Estera, Kalinowski Paweł, Bojakowska Urszula. Czynniki ryzyka zakażenia HCV oraz metody profilaktyki = Risk factors of HCV infection and methods of prevention. Journal of Education, Health and Sport. 2016;6(1):327-332. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45400 http://ojs.ukw.edu.pl/index.php/johs/article/view/3359 https://pbn.nauka.gov.pl/works/710941     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016.       Czynniki ryzyka zakażenia HCV oraz metody profilaktyki Risk factors of HCV infection and methods of prevention   Marta Estera Kowalska, Paweł Kalinowski, Urszula Bojakowska   Samodzielna Pracownia Epidemiologii Uniwersytetu Medycznego w Lublinie Independent Epidemiology Unit, Medical University of Lublin           dr n. o zdr. Marta Estera Kowalska, dr hab. n. med. Paweł Kalinowski, mgr Urszula Bojakowska Samodzielna Pracownia Epidemiologii Uniwersytetu Medycznego w Lublinie Independent Epidemiology Unit, Medical University of Lublin       Słowa kluczowe: wirusowe zapalenie wątroby typu C, edukacja, profilaktyka. Key words: hepatitis C, education, prevention.   Streszczenie Wirusowe zapalenie wątroby typu C stanowi obecnie jedno z największych zagrożeń epidemiologicznych, które wymaga skutecznych działań w zakresie profilaktyki, edukacji społeczeństwa w tym zakresie oraz poprawy dostępności do nowych metod terapeutycznych. Poznając czynniki ryzyka oraz grupy populacji o wysokim ryzyku zakażenia HCV, profilaktyka w tym zakresie może być bardziej skuteczna. Celem pracy jest przedstawienie dróg przenoszenia wirusa oraz metod zapobiegania zakażeń HCV.   Summary Hepatitis C is one of the greatest epidemiological threats at present which requires effective actions in the prevention and education of the society in this respect and improved access to therapeutic new methods. Recognizing the risk factors and population groups at high risk of HCV infection prevention in this area can be more effective. The aim of this study was to present the routes of transmission and methods of prevention of HCV infection.